RANCANG BANGUN RING UPRIGHT DARKFIELD MICROSCOPE UNTUK MENGHASILKAN VISUAL MIKROGRAFI DAPHNIA MAGNA DLM PRAKT TEK LAB - Sulistiyawati Sulistiyawati (Integrated Lab Journal, 2019)
Design research of upright darkfield microscope to produce visual micrography of Daphnia magna in laboratory engineering practicum carried out at the Biology Laboratory of the Faculty of Science and Technology at UINSunan Kalijaga. The purpose of this study is to document Daphnia magna using the darkfield observation method. The darkfield method is obtained by making a darkfield condenser ring on an upright brightfield microscope which in its application can change the observation method on a microscope from brightfield to darkfield. The results of this study are in the form of Daphnia magna with the darkfield and brightfield method which this method can be applied in laboratory engineering labs.